О некоторых вопросах перевода произведений И.Э. Бабеля на венгерский язык - Sandor Vegvari (Slavica TerGestina, 1997)
The author of the study first examines those common features of Isaac Babel's literary works which determine the possibility of translation; later he mentions some characteristic notions of Hungarian translators, Hungarian publications and the premises for the reaction to them. In connection with the translation of concrete works the author points out cases of mistranslation, which are luckily not too many, then analyses the cases in detail in which the translator's task is more or less difficult. He indicates typical cases where adequate and precise translation becomes impossible: he refers to phraseologism and cases of word-by-word Russian translation from Yiddish.